Jasna Jeličić Radonić and Miroslav Katić. Faros – osnivanje grčkog grada – I, (Pharos - the foundation of the ancient city – I). - Kirigin, Branko (Journal of Greek Archaeology, 2018)
This review would not have been necessary if this book did not have an extensive English summary, almost as long as the entire text in Croatian (the book’s cover lacks the English title). The aim of Jeličić-Radonić and Katić’s book is to introduce us to ten years (1994-2004) of archaeological excavations conducted at Stari Grad on the Adriatic island of Hvar in Croatia, where the remains of Pharos (a Greek polis founded in the early 4th century BC) are located. Their book has fourteen unnumbered chapters as well as an Introduction, Conclusions, a Bibliography and an Index. I will only mention here some of the problems found in this book, whose publication has long been announced and awaited.